Galvano- and thermo-magnetic effects at low and high temperatures within non-Markovian quantum Langevin approach; Physica A: Statistical Mechanics and its Applications; Vol. 508 - Abdurakhmanov I. B. Ilkhom; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Kanokov Z. Zakirzhon (2018, 2018)
Title screen